Pengaruh Persepsi Kualitas dan Kesadaran Merek terhadap Minat Beli Konsumen pada Merek Fashion Lokal Colorbox (Studi pada Mahasiswa di Kota Malang) - Aurinisa, Nadiandisa Candara; Eko Boedhi Santoso; Achmad Zaini (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The fashion industry in Indonesia has been growing rapidly and significantly. It is because clothing fashion has become a part of lifestyle that cannot be separated form daily use. The perceived quality and brand awareness are the things that companies need to focus on to see the intensity of the consumer purchase intention. The perceived quality influences consumers perception about the quality of product or brand that they first see. Meanwhile, the brand awareness sees how far consumers know the brand. This research aims to analyze the influence of perceived quality and brand awareness on purchase intention in local fashion brand, Colorbox (study on college students in Malang City). The research approach was quantitative with an explanatory research design through a survey. The research showed a positive and significant effect on purchase intention. Then the hypothesis testing result that perceived quality and brand awareness had a positive and significant effect on purchase intention.